Two new genera and five new species of Mugadina-like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions - Ewart, A. (Zootaxa, 2018)
Moulds (2012) established the genus Mugadina for two small cicadas, M. marshalli (Distant) and M. emma (Goding and Froggatt), both grass inhabiting species known from Queensland and New South Wales. Both species are notable for their relatively simple 'ticking' songs. Moulds further noted that there were at least two superficially similar genera of cicadas, but each with different genitalia. This paper describes two new genera of small (9–15 mm body lengths) and distinctive grass cicadas with genitalia that are very similar to those of Mugadina, but possess clear morphological, colour and calling song differences. The new genera are: Heremusina n. gen. with two known species namely H. udeoecetes n. sp. and H. pipatio n. sp.; the second new genus is Xeropsalta n. gen., containing four known species, X. thomsoni n. sp., X. aridula n. sp., X. rattrayi n. sp., and X. festiva n. comb. Heremusina n. gen. species are described from the Alice Springs area of Northern Territory and the Cloncurry area of northwest Queensland, from arid to semi arid habitats. The Xeropsalta n. gen. species are described from western, southwest and central Queensland, and from the Simpson and Strzelecki Deserts in northeastern South Australia and northwestern New South Wales, respectively, all locations in very arid to arid habitats, but close to seasonal (often irregular) rivers and lakes. X. festiva n. comb. occurs in semi arid habitats in southern and southeastern Australia.        Detailed taxonomic descriptions are provided of the new species, together with distributions, habitats, and the calling songs. The Heremusina species emit songs with short repetitive buzzing echemes, the echeme durations differing between each species. The Xeropsalta songs are notable for their complexity, containing multiple elements with rapid changes of amplitudes and temporal structures, rather atypical of the songs of most small grass dwelling cicadas. Detailed song structures distinguishing each of the species are illustrated and interpreted in each case in light of their respective taxonomic status.